SIMULATION OF THE SEVERE PLASTIC DEFORMATION PROCESS IN NANOCRYSTAL ON THE BASIS OF INTERMETALLIDE - E.A. Dudnik (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2012)
The mechanisms of structural transitions in a nanocrystal on the basis of intermetallic Ni3Al was studied by means of simulation of the process of the severe plastic deformation. For the structure analysis we used the simplexes of Voronoi-Delaunay, which allow tracing the dynamics of the formation of ordered areas in the process of deformation.